Porphyria turcica: a survey of 592 cases of cutaneous porphyria seen in southeastern Turkey - Doğramacı, İhsan and Wray, Joe D. and Ergene, Turhan and Sezer, Vedat and Müftü, Yunus (The Turkish Journal of Pediatrics, 1962)
A comprehensive report of a field survey, covering 592 cases of porphyria turcica, the cutaneous porphyria seen in southeastern Turkey, is presented. The basic plan of the survey is described and the results with regard to presenting signs and symptoms and the epidemiologic pattern of the disease are set forth in the text and in tabular form. The evidence uncovered in the survey is weighed against information derived from a group of over 3,000 nonaffected children living in the same region, especially in regard to nutritional status as judged by weight and height measurements. It is concluded that weakness, cutaneous photosensitivity and porphyrinuria are the most common presenting features of the disease, followed by hypertrichosis and hyperpigmentation which are eventually manifested by the majority of patients. Neurologic symptoms do not seem to be a feature of this form of porphyria but abdominal pain was reported in some cases and liver enlargement was found to be present in 33 per cent of the cases surveyed. The remarkable finding of arthritic changes in 36.1 per cent of the patients in the early stages of the disease is reported, together with the later finding that the incidence of arthritic changes had risen to 54.8 per cent at the end of another two and a half year interval during which time other signs diminished. The peak incidence of the disease was found to be in the 6 to 10 year age group, followed by the 11 to 15 year group. Sex differences were not found to be significant. All patients reported seasonal fluctuations in the course of the disease.